Massive open online courses (MOOCS): systematic literature review in Malaysian higher education - Al-Rahmi, Waleed; Aldraiweesh, Ahmed; Yahaya, Noraffandy; Bin Kamin, Yusri (International Journal of Engineering and Technology, 2018)
This study provided a systematic and organized review of 32 studies regarding using of Massive Open Online Courses (MOOCs) in Ma-laysian higher education from 2012 to 2017. This paper conducted an analysis of studies dedicated of using (MOOCs) for learning on the basis of certain dimensions namely, journal, country, author, year of publication, research methods, type of respondents, the models, and the theories. The findings obtained revealed that the interest on the topic has shown an increasing trend over recent years that it has ultimately become a well-known topic for academic research in the future. Nevertheless, to boost and enhance the using (MOOCs) for learning, it is important that future studies apply considerable use of theoretical and methodological approaches like the qualitative methods to examine the factors it will encourage students to use (MOOCs).Â Â